COMPARATIVE EFFICACY OF INTRACORONARY VERAPAMIL AND ADRENALINE IN MANAGING CORONARY NO-REFLOW DURING PRIMARY PCI IN STEMI PATIENTS AT A TERTIARY CARE HOSPITAL - KHAN, S; REHMAN, SU; SAJJAD, W; BEGUM, S; YASMIN, R; ADIL, IU (Biological and Clinical Sciences Research Journal, 2024)
Coronary No-Reflow (CNR) is a significant complication during Primary Percutaneous Coronary Intervention (PPCI) for ST-Elevation Myocardial Infarction (STEMI), often leading to poor clinical outcomes. Management strategies for CNR include various pharmacological agents, among which intracoronary verapamil and intracoronary adrenaline are commonly used alongside Glycoprotein IIb/IIIa inhibitors. Objective: This study aims to compare the effectiveness of intracoronary verapamil versus intracoronary adrenaline, alongside Glycoprotein IIb/IIIa inhibitors, in managing Coronary No-Reflow (CNR) during Primary Percutaneous Coronary Intervention (PPC1) for STEMI patients. Methodology: This randomized-control-trial was conducted at the Department of Cardiology, MTI Lady Reading Hospital Peshawar, Pakistan, from May 2023 to April 2024. Fifty patients diagnosed with CNR during PPC1 were randomised into two groups: adrenaline and verapamil. The primary outcome measures were TIMI Flow Grade (TFG) and Myocardial Blush Grade (MBG) immediately post-intervention. In contrast, secondary outcomes included Major Adverse Cardiovascular Events (MACE), myocardial infarction, stroke, target vessel revascularisation, mortality, and Left Ventricular Ejection Fraction (LVEF) assessed at baseline and one-month follow-up. Statistical analyses were performed using IBM SPSS version 20, with significance at P<0.05. Results: Baseline characteristics, procedural details, and initial TIMI flow grades were similar between groups. Adrenaline achieved universal TIMI 3 flow compared to 84% with verapamil (p=0.049), but no significant differences were noted in myocardial blush grades. Adrenaline led to significantly higher follow-up LVEF (45.0 ± 9.0 vs. 39.0 ± 9.0, p=0.027) and a more significant percentage change in LVEF (20.97% vs. 8.94%, p=0.042) than verapamil. Adverse event rates were comparable except for lower MACE incidence at 30 days with adrenaline (8.0% vs. 24.0%, p=0.039). Conclusion: Adrenaline notably enhanced TIMI 3 flow rates, improved left ventricular ejection fraction, and decreased significant adverse cardiovascular events at 30 days compared to verapamil. These findings suggest that adrenaline may be a superior option for improving coronary blood flow and early clinical outcomes in this patient population.